1982
DOI: 10.1002/1520-6629(198201)10:1<29::aid-jcop2290100105>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of adjustment problems in preschool children by teachers and paraprofessional aides

Abstract: Differences in perception between college student aides' and teachers' judgments of a child's problems, and how well they know and like the child, were investigated. The AML and CARS scales were used by both teachers and aides to evaluate three‐ and four‐year‐old children referred to a preschool mental health project. Statistically significant differences were found between teachers' and aides' perceptions, with the aides being generally more positive in their assessments of the children. To the extent that a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1984
1984
1986
1986

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Since it has been found that nursery nurses and paraprofessional aides are more 'tender-minded' than teachers about the children in their care (Gipps, 1982b;Katz, 1971;Rickel, 1982), their ratings were compared. There were 68 teacher/nursery nurse pairs of PBCL scores, from the combined centre and one nursery class.…”
Section: Role and Qualificationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since it has been found that nursery nurses and paraprofessional aides are more 'tender-minded' than teachers about the children in their care (Gipps, 1982b;Katz, 1971;Rickel, 1982), their ratings were compared. There were 68 teacher/nursery nurse pairs of PBCL scores, from the combined centre and one nursery class.…”
Section: Role and Qualificationsmentioning
confidence: 99%
“…There is a wide range of different preschool facilities, staffed with adults who frequently have quite dispEirate backgrounds in terms of experience and qualifications, and who perceive their roles quite differently (Gipps, 1982a), and we wished to examine the applicability of our scale in different settings. It has been found in the U.S.A. that paraprofessioncd aides are more positive about children than teachers (Rickel, 1982) and that staff in low status jobs are more subjective about the qualities of the children in their care (Katz, 1971). In a British study it was found that the ratings of verbal-social skills made by nursery nurses who worked in day nurseries were positively correlated with their attitudes about the children, while this was not the case for nursery nurses in schools, or for teachers (Gipps, 1982b).…”
Section: Introductionmentioning
confidence: 99%